The Analysis of Rice Farmers' Business Income in Pape Village, Bajawa District, Ngada Regency - Densiana Lati; Johanes Besin; M Syahrun (Economics and Education Journal (Ecoducation), 2020)
Farming is the study of how farmers coordinate and group production factors as effectively and efficiently as possible in order to benefit farmers. Effective means producers or farmers who make the best use of their resources, while efficient is the use of resources that can produce less output than inputs. This study aims to determine the sales process of paddy farmers in Pape Village and the income of paddy farmers earned by the people of Pape Village. This research uses a qualitative approach. Retrieval of research data using observation, interviews, and documentation. Based on the results of the study it can be concluded that the total area of farmers in Pape Village is 1,000 acres (1/4 hectare) if the average area of informants is 25 acres (1/4 hectare). The profits of farmers vary greatly from the informant's land area. From the results of interviews with informants that the land condition in Pape Village is very good for rice farmers, because farmers use irrigation channels in rice fields even in the dry season. Thus the harvest can be stored and sold.